Palladium-catalyzed three-component reaction for the synthesis of 3, 3-disubstituted allylic alcohols with regio- and stereoselectivity. (5th January 2018) - Hu, Gang; Wang, Jingtao; Li, Zefei; Liu, Yajing; Gong, Ping
Abstract : A novel three-component assembly of allenic alcohols, aryl iodides and 1, 3-dicarbonyl compounds into 3, 3-disubstituted allylic alcohols was promoted in the presence of a palladium source. Abstract : A novel three-component assembly of allenic alcohols, aryl iodides and 1, 3-dicarbonyl compounds into 3, 3-disubstituted allylic alcohols was promoted in the presence of a palladium source. A plausible mechanism through Pd 0 catalysis was established to explain the regio- and stereoselectivity. Various aryl iodides and functionalized dicarbonyls were well-tolerated to afford products in good to moderate yields.